Hemodynamic and Clinical Outcomes of Milrinone Compared to Dobutamine in Cardiogenic Shock: A-Systematic Review and Meta-Analysis - Bahagia, William; Santoso, Jimmy Oi (The Indonesian Heart Association, 2022)
Background Despite years of clinical experience with the two most commonly used inotropes i.e dobutamine and milrinone, in the cardiogenic shock setting, there is a lack of head-to-head comparison between inotropes in cardiogenic shock. We conducted a systematic review and meta-analysis on the comparison of hemodynamic and clinical effects of dobutamine and milrinone in cardiogenic shock. Methods A comprehensive literature search using PubMed and Scopus was performed. Among 40 studies retrieved from the database, 3 studies were included for hemodynamic comparison outcome and 2 studies for clinical outcomes. Results Three studies with 101 patients were included for hemodynamic analysis and two studies with 146 patients for clinical analysis. We observed no significant difference between cardiac index, pulmonary capillary wedge pressure, and mean arterial pressure at 1 hour after milrinone and dobutamine administration. However, there is significantly lower mPAP after milrinone infusion compared to dobutamine (mean difference -8,7 (-9,97 to -7,43) mmHg, p<0,01). We also observed no significant difference in in-hospital mortality but significantly shorter ICU length of stay in the milrinone group (mean difference -1 (-1,92 to -0,08) days). Conclusion Administration of milrinone resulted in lower PA pressure and shorter ICU LOS compared to dobutamine in patients with cardiogenic shock. This article has a related Erratum.